A crystalline and 3D periodically ordered mesoporous quaternary semiconductor for photocatalytic hydrogen generation. Issue 7 (31st January 2018) - Weller, Tobias; Deilmann, Leonie; Timm, Jana; Dörr, Tobias S.; Beaucage, Peter A.; Cherevan, Alexey S.; Wiesner, Ulrich B.; Eder, Dominik; Marschall, Roland
Abstract : The first crystalline and 3D periodically ordered mesoporous quaternary semiconductor for photocatalytic hydrogen production has been prepared. Abstract : We have prepared the first crystalline and 3D periodically ordered mesoporous quaternary semiconductor photocatalyst in an evaporation-induced self-assembly assisted soft-templating process. Using lab synthesized triblock-terpolymer poly(isoprene- b -styrene- b -ethylene oxide) (ISO) a highly ordered 3D interconnected alternating gyroid morphology was achieved exhibiting near and long-range order, as evidenced by small angle X-ray scattering (SAXS) and electron microscopy (TEM/SEM). Moreover, we reveal the formation process on the phase-pure construction of the material's pore-walls with its high crystallinity, which proceeds along a highly stable W 5+ compound, by both in situ and ex situ analyses, including X-ray powder diffraction (XRPD), Fourier transform infrared spectroscopy (FTIR) and electron paramagnetic resonance (EPR). The resulting photocatalyst CsTaWO6 with its optimum balance between surface area and ordered mesoporosity ultimately shows superior hydrogen evolution rates over its non-ordered reference in photocatalytic hydrogen production. This work will help to advance new self-assembly preparation pathways towards multi-element multifunctional compounds for different applications, including improved battery and sensor electrode materials.